2019
DOI: 10.1155/2019/6032631
|View full text |Cite
|
Sign up to set email alerts
|

LCZ696 Therapy Reduces Ventricular Tachyarrhythmia Inducibility in a Myocardial Infarction-Induced Heart Failure Rat Model

Abstract: Background. LCZ696 (valsartan/sacubitril) therapy significantly reduced mortality in patients with heart failure (HF). Although a clinical trial (PARADISE-MI Trial) has been ongoing to examine the effects of LCZ696 in myocardial infarction (MI) patients, the effects of LCZ696 on remodeling of cardiac electrophysiology in animal models remain largely unclear. Methods. We performed coronary artery ligation to create MI in Sprague-Dawley rats. Echocardiography was performed one week after MI to confirm the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Activation of STAT1 has been demonstrated to induce cardiomyocyte apoptosis following ischemia/reperfusion injury by enhancing the expression of pro-apoptotic proteins, which suggests that STAT1 plays a key role in the pathology of MI ( 68 70 ). AKT3 is involved in cardiomyocyte cell death ( 71 ). In rats, the expression of AKT3 is decreased in the spinal cord following myocardial ischemia-reperfusion injury ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of STAT1 has been demonstrated to induce cardiomyocyte apoptosis following ischemia/reperfusion injury by enhancing the expression of pro-apoptotic proteins, which suggests that STAT1 plays a key role in the pathology of MI ( 68 70 ). AKT3 is involved in cardiomyocyte cell death ( 71 ). In rats, the expression of AKT3 is decreased in the spinal cord following myocardial ischemia-reperfusion injury ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the underlying mechanism of sacubitril/valsartan remains unclear, the activated NP system promotes left ventricular reverse remodeling and reduced myocardial fibrosis, which may prevent the development of fatal arrhythmias [22]. Moreover, sacubitril/valsartan reduced the inducibility of ventricular arrhythmia and restored the expression of downregulated potassium channels in an experimental model of myocardial infarction in rats [23]. These results identify possible mechanisms associated with the reduced sudden cardiac death observed in the sacubitril/valsartan treatment groups.…”
Section: Results From Randomized Controlled Trials Of Angiotensin Recmentioning
confidence: 73%
“…25 In addition to remodelling of ventricular hypertrophy, ion channels play an essential role in modulating the cardiac action potential for electrical conduction throughout the hypertrophic heart. 26 In respect of systolic HF rat model, Chang et al 9 observed that LCZ696 could up-regulate expression of K + channel proteins, including KCNH2, KCNE1, and KCNE 2, which caused shortened APD and ameliorated ventricle arrhythmogeneity of myocardial infarction-related HF. In contrast, in the SHR group, we observed up-regulation of tissue expression of small-conductance Ca 2+ -activated K + (SK and K Ca 2).…”
Section: Discussionmentioning
confidence: 99%
“…SV is a first‐in‐class medicine that has been proven to minimize the risk of non‐sustained and sustained ventricular tachycardia in HFrEF patients 7,8 . Previous studies have shown that LCZ696 improves systolic function, electrophysiological benefits, and down‐regulation of sodium and potassium channel protein expression, which are important contributors to systolic dysfunction‐related ventricular arrhythmia 9,10 . On the other hand, the rate of sudden cardiac death (SCD) is 0.3 per 100 patient‐years in hypertensive patients without cardiovascular diease 11 .…”
Section: Introductionmentioning
confidence: 99%